The Influence of School Principal Leadership, Family Environment, and Learning Motivation on Student Learning Outcomes at State Junior High School 1 and 3 Tareran - Rumengan, Meylan Meyti; Wullur, Mozes Markus; Lengkong , Jeffry Sony Junus (International Journal of Information Technology and Education, 2023)
Student learning outcomes are the main problem in this research. This research aims to analyze the influence of the principal's leadership, family environment, and learning motivation on student learning outcomes at State Junior High School 1 and 3 Tareran. This type of research uses a survey research method with a quantitative research approach and is analyzed using descriptive data analysis as well as percentages and multiple linear regression. The research population was 283 respondents and the sample was 57 respondents using probability sampling techniques. The data collection technique used consists of distributing questionnaires and documentation of student learning outcomes. The results of the analysis show that there is a significant and positive influence between the variables of principal leadership, family environment, and learning motivation on student learning outcomes in the two secondary schools. The family environment variable has the greatest influence at 20.25%, followed by the principal's leadership at 12.39%. and learning motivation of 7.29%.